Somos fruto da nossa socialização: a influência das crenças pessoais no comprometimento organizacional - Ribas, Fabio Teodoro Tolfo (2010)
Often, organizations are will with problems that can be either internal or external, which can cause multiple consequences. By studying the relationship of personal values on organizational commitment is proposed to identify and understand the types of beliefs that are related to specific types of linkages prevailing in a sample of employees from various companies in the city of South Boxes The study presents a predominantly quantitative approach, descriptive in nature. The instrument used for data collection was composed of three parts. The first part aimed to identify the profile of the sample investigated, the second part, based on Monday, Porter and Steers (1979) and also Meyer, Allen and Smith (1991) tried to verify aspects related to organizational commitment and the third part, developed from the study of Gouveia (2003) aimed at identifying the human values. Data analysis tests were performed descriptive statistics, correlations between personal values and constructs of organizational commitment and application of regression models, including analysis of the mean, median and standard deviation, was also performed internal consistency of the subsystems of values and personal constructs of organizational commitment, and reliability of these from the Cronbach's Alphas. The relevance of this issue is guided by previous research demonstrating the importance of personal values as a mechanism for explanation of various socio-psychological phenomena, so we attempted to find relationships in the workplace between individual beliefs (personal values) on the different types of links ( organizational commitment) with the organization. The results showed that the models obtained nnhum despite meet the statistical assumptions, showed a high degree of explanation, indicating that the values studied did not contribute significantly to the understanding of the commitment of employees.